Education Business Innovation in Indonesia: Challenges and Opportunities - Anastasia*, Jessica; Agustino, Antonius; Setyawan, Filippus Cahyo; Naibaho, Nora; Fathurrahman, R. Muh. Syakur; Setiadi, Teguh; Amalia, R. Nur; Tarumingkeng, Lingkan; Saptaji, Delli; Julianti, Metri; Tangkudung, Audrey G; Pakpahan, Marisi; Rante, Jones Zenas (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
Education business innovation is an important solution to face challenges and capitalize on opportunities in the evolving world of education, especially in Indonesia. In a dynamic global context, education business innovation is key to shaping an education future that is bright, sustainable and has a positive impact on society and individuals. The purpose of this research is to identify innovations and analyze the challenges and prospects of education, and through the adoption of successful education business innovations, Indonesia can shape an inclusive, relevant and quality education system, preparing individuals to face global challenges and seize future opportunities. In this research, we examine various aspects of education business innovation, including education technology, project-based learning, collaboration with industry, development of distance education models, and enhancement of soft skills. We also discuss challenges such as resistance to change, infrastructure limitations, the digital divide, complex regulations and data privacy concerns, and propose how education business innovation can help overcome these barriers. By adopting successful education business innovation, Indonesia has the potential to create a more inclusive, relevant, and quality education system that prepares individuals to face global challenges and capitalize on future opportunities. Education business innovation is the key to shaping an education future that is bright, sustainable and positively impacts society and individuals.